(untitled) (Journal of Comparative Social Work, 2007)
Internationally, Canadians struggle with their national identity. Canadians proclaim that they are not Americans and like to boast that they have more in common with Sweden with its snowy winters and extensive social programmes. This article outlines some of the historical developments of social welfare in Canada and examines some of the recent trends at dismantling the programmes. In the neo-conservative state, efforts towards “globalization” and “free trade” with the United States have attacked Canada’s social safety net, marginalizing and suppressing the poor. However, in spite of the current trends, Canadians have maintained its humanitarian philosophy and resisted the “Americanization” of its social programmes. Some of this resistance has been successful but as in many other countries much of it has failed.